Effects of global warming on reindeer husbandry in the Swedish subarctic : correlations across microclimatic change, subarctic vegetation cover, and reindeer foraging preferences - Fusté Ballesteros, Jordi (SLU/Dept. of Energy and Technology, 2010)
The Abisko Scientific Research Station (ANS) is located in the far north of Sweden, in a subarctic environment inhabited mostly by the Sami people. ANS has conducted research for more than hundred years, with its current focus set on interdisciplinary research regarding the effects of climate-change on the subarctic environment.